The Influence of Social Media Marketing on Purchase Intention Mediated by Electronic Word of Mouth: a Bibliometric Analysis - Hikmawati, Kuncoro Aprilia; Soetjipto, Budi Eko; Wardhana, Ludi Wishnu (Economics and Business Journal (ECBIS), 2025)
This study examines the influence of social media marketing on purchase intention through electronic word of mouth (eWOM). In today's era, eWOM has become one of the key factors influencing consumers" purchase intentions, as information shared online can either strengthen or weaken a consumer" 's purchase intention. This research uses bibliometric analysis with data from the Scopus database to explore existing research trends and the relationship between social media marketing, eWOM, and purchase intention. The findings show that social media marketing significantly impacts purchase intention through eWOM as a mediator that strengthens this influence. This study provides valuable insights for marketers and the general public, especially in designing strategies that leverage eWOM to enhance social media marketing activities and increase purchase intention.